Coastal groundwater aquifer characterization from geoelectrical measurements- A case study at Kalapara, Patuakhali, Bangladesh. - Mohammad Ibrahim Khalil; S. M. Didar-Ul Islam; Md. Jamal Uddin; Ratan Kumar Majumder (Journal of Applied Geology, 2020)
Vertical electrical sounding has been carried out in a coastal area in the southern part of Bangladesh to locate the groundwater aquifers containing fresh water. The Interpex1X1Dv3 computer program was used to process the field apparent resistivity data sets obtained from the vertical electrical sounding.  Geoelectric layers were identified in the context of resistivity and thickness from the vertical electrical sounding data. From the initial parameters layered model was achieved using the inversion technique. Correlation of the obtained layer model with a nearby lithologic log concludes the groundwater aquifer system of the area. From the electrical properties of the subsurface layers, water bearing layers were detected and characterized. Very fine sand geoelectric layer with a thickness varying from 20 to 143 meters is an upper aquifer and has 0.66–14.02 Ωm apparent resistivity value. Fine sand geoelectric layer with 0.21-5.99 Ωm apparent resistivity value is lower aquifer with maximum thickness ~250 meters. From the resistivity value, it is observed that the upper aquifer contains saline to brackish-fresh water while the resistivity value of the lower aquifer indicates that it contains saline water. The water quality of the upper zone varies geographically from the southern to the northern part in the investigated area. The water quality of the upper aquifer is fresh in the northern part of the study while lower aquifer contains saline water there.